Regulation of the Immune System in Aging: Focus on Epigenetic Mechanisms - K. A. Aitbaev; I. T. Murkamilov; Zh. A. Murkamilova; I. O. Kudaibergenova; F. A. Yusupov (SINAPS LLC, 2022)
Epigenetics studies processes leading to changes in the activity of genes without changing the DNA sequence. Epigenetic mechanisms, such as DNA methylation and histone modifications, are formed during embryonic development, and epigenetic profiles are stably inherited in mitosis, providing cell differentiation and their further fate in the development process. Under the influence of internal and external factors such as metabolic profile, hormones, nutrition, drugs, smoking and stress, epigenetic mechanisms are actively modulated and, in this sense, a lifestyle can significantly affect the epigenome, and consequently, the gene expression profile and function of cells. It is shown that the development and function of cells of both congenital and adaptive immune systems are also regulated by epigenetic mechanisms, and negative epigenetic changes are a distinctive feature of aging and cancer. Given these data, it can be assumed that age-related changes in the profile of epigenetic labels can lead to a decrease in immune function and contribute to an increase in morbidity in the elderly. Therefore, to ensure healthy aging, better understanding of how to avoid epigenetic changes that are associated with aging of the immune system is needed. In this review, we tried to generalize the latest achievements in this field of research and consider the possibility of using them for diagnosis, prevention and treatment of diseases.